What are we saying when we talk about Sustainability? - Toledo, Victor Manuel (Revista Internacional de Salarios Dignos, 2020)
If you consider 1987 (the Brundtland Report) as the official beginning of the idea of sustainability, the term has made a brilliant journey of almost three decades and is still alive. In its evolution, it has become at the same time a concept, paradigm, theoretical framework, technical instrument, utopia, pretext, ideology and many other things, but above all it has become the word that contains a vague desire of the educated and privileged masses of the planet for a better world in which the human race rediscovers itself ideally with nature and with social justice. Beyond the ideological dimension, and its multiple and ungraspable interpretations, this essay focuses on sustainability as a scientific concept that springs from an interdisciplinary vision of reality, and that for many authors achieves the status of a new paradigm. The essay attempts to show how the scientific concept of sustainability in the vast majority of its versions, is not but a techno-economic expression that explicitly or implicitly is aimed at convincing the "decision makers", and that seeks to apply solutions merely technical. Using a political ecological approach, based on the theory of the three powers, the essay identifies and develops a definition of sustainability as a social power, which turns the concept into a promising political instrument of social and environmental emancipation, in a legitimate version of a "science with conscience”.